2019
DOI: 10.1536/ihj.19-131
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Alleviates Atrial Inflammation, Remodeling, and Vulnerability to Atrial Fibrillation after Myocardial Infarction

Abstract: Atrial inflammation and fibrosis are the critical processes involved in atrial fibrillation (AF) after myocardial infarction (MI). Fisetin is a dietary flavonoid that has shown forceful anti-inflammatory and antiproliferative properties in diverse models of disease. However, fisetin's role in atrial inflammation, fibrosis, and AF vulnerability post-MI remains completely unknown. Rats were subjected to MI surgery, by left anterior descending coronary artery ligation or sham operation, and treated with DMSO or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…NF-κB is the primary regulator of the appearance of SASP, the activation of AMPK can inhibit NF-κB signaling and inflammation (Salminen et al, 2011). Some reports have established the role of FIS in regulating AMPK/NF-κB signaling pathways (Liu et al, 2019;Yang W. et al, 2019). Consistently, our results revealed that FIS could activate AMPK and inhibit NF-κB activity both in vivo and in vitro, whereas such changes were partly blocked by AMPK inhibitor, accompanied by elevated senescence markers.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…NF-κB is the primary regulator of the appearance of SASP, the activation of AMPK can inhibit NF-κB signaling and inflammation (Salminen et al, 2011). Some reports have established the role of FIS in regulating AMPK/NF-κB signaling pathways (Liu et al, 2019;Yang W. et al, 2019). Consistently, our results revealed that FIS could activate AMPK and inhibit NF-κB activity both in vivo and in vitro, whereas such changes were partly blocked by AMPK inhibitor, accompanied by elevated senescence markers.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that FIS supplementation prevents hepatic fibrosis by suppressing the gene expressions of COL1, MMP2, MMP3, and MMP9 and collagen accumulation (Choi et al, 2020). FIS treatment markedly reduces the expression of fibrosis-related genes and inhibits myocardial fibrosis by inactivating TGF-β/Smads signaling (Liu et al, 2019;Hu et al, 2020). More importantly, no side effects of FIS have been reported, even when given at high doses (Maher, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase of reactive oxygen species during AMI leads to the occurrence of oxidative stress injury, resulting in myocardial cell death and tissue damage [ 11 , 12 ]. When inflammatory response occurs after myocardial infarction, inflammatory cytokines are released and the numbers of macrophages gradually increase, provoking further myocardial damage [ 13 ]. However, antioxidant stress response and anti-inflammatory may prevent these harmful events and attenuate myocardial dysfunctions [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,4) Existing experimental evidence and clinical data indicate that a variety of factors are involved in the process of myocardial fibrosis and AF, including oxidative stress, calcium overload, inflammation, and the activation of cardiac fibroblasts. [5][6][7] Myocardial fibrosis plays a key role in the maintenance of arrhythmia, which can cause cardiac remodeling, affect the diastolic and contractile functions of the heart, and even cause malignant arrhythmias and sudden cardiac death. 8,9) The content and distribution of cardiac fibrotic tissue in patients with AF are related to the mechanism of AF, the risk of complications, and the effect of treatment.…”
mentioning
confidence: 99%